Gender articulated: language and the socially constructed self - Hall, Kira; Bucholtz, Mary (Routledge, 1995)
Gender Articulated is a groundbreaking work of sociolinguistics that forges new connections between language-related fields and feminist theory. Refuting apolitical, essentialist perspectives on language and gender, the essays presented here examine a range of cultures, languages and settings. They explicitly connect feminist theory to language research. Some of the most distinguished scholars working in the field of language and gender today discuss such topics as Japanese women's appropriation of "men's language," the literary representation of lesbian discourse, the silencing of women on the Internet, cultural mediation and Spanish use at New Mexican weddings and the uses of silence in the Anita Hill-Clarence Thomas hearings.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; langage; lin2685; linguistique; maternité; premier cycle; queer; sciences humaines; sociolinguistique; thématiques; études de genres

Of woman born: Motherhood as experience and institution - Rich, Adrienne (Norton, 1995)
Adrienne Rich's influential and landmark investigation concerns both the experience and the institution of motherhood. The experience is her own—as a woman, a poet, a feminist, and a mother—but it is an experience determined by the institution, imposed on all women everywhere. She draws on personal materials, history, research, and literature to create a document of universal importance. Dans Of Woman Born , initialement publié en 1976, la poétesse et féministe influente Adrienne Rich examine les systèmes patriarcaux et les institutions politiques qui définissent la maternité. En explorant sa propre expérience - en tant que femme, poète, féministe et mère - elle trouve que l'acte de materner est à la fois déterminé par et distinct de l'institution de la maternité telle qu'elle est imposée à toutes les femmes partout dans le monde
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; corps; cours; discours dominant; fem1000; maternité; premier cycle; périodes historiques; régions géographiques; santé; systèmes d'oppressions; thématiques; théories féministes; états-unis